OPTIMIZATION OF AL-QUR'AN LEARNING THROUGH THE QIROATI METHOD STUDY OF EFFECTIVENESS AT TPQ SYAMSUL QURA - Salis Filzati Faiqah; Ansharuddin M (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
This research is motivated by the importance of mastering the ability to read the Qur’an correctly from an early age, which serves as a fundamental basis for forming Islamic character. Taman Pendidikan Al-Qur’an (TPQ) as a non-formal Islamic educational institution, plays a strategic role in developing Qur’anic literacy among children. However, several challenges are still encountered in its implementation, including the accuracy of recitation, understanding of tajweed rules, and students' learning motivation. Therefore, this study aims to evaluate the effectiveness of the Qiroati method in optimizing Qur’anic learning at TPQ. The Qiroati method is known as a systematic Qur’anic learning approach that emphasizes gradual instruction, hands-on practice, and early tajweed reinforcement. This study uses a descriptive qualitative approach, with data collected through classroom observation, in-depth interviews with teachers and students, and documentation of learning outcomes. The subjects of the study included teachers and students of TPQ who had been using the Qiroati method for at least six months. The findings indicate that the Qiroati method positively impacts students’ Qur’anic reading abilities. Improvements were observed in accurate pronunciation, basic understanding of tajweed rules, and reading fluency without spelling. In addition, the method boosts students’ confidence and enthusiasm for learning. Supporting factors of its effectiveness include well-trained instructors, structured use of Qiroati textbooks, and active parental involvement at home. However, some obstacles were also identified, such as varying initial abilities among students, limited learning time, and a lack of interactive learning media. The study concludes that the Qiroati method is effective in optimizing Qur’anic learning, although improvements in teaching facilities and more diverse instructional strategies are recommended. It is hoped that this research can serve as a reference for other TPQ seeking to implement the Qiroati method to enhance the quality of Qur’anic education in the community